Induction of long-lasting multi-specific CD8+ T cells by a four-component DNA-MVA/HIVA-RENTA candidate HIV-1 vaccine in rhesus macaques. - Im, E; Nkolola, J; di Gleria, K; Mcmichael, A; Hanke, T (2006)
As a part of a long-term effort to develop vaccine against HIV-1 clade A inducing protective T cell responses in humans, we run mutually complementing studies in humans and non-human primates (NHP) with the aim to maximize vaccine immunogenicity. The candidate vaccine under development has four components, pTHr.HIVA and pTH.RENTA DNA, and modified vaccinia virus Ankara (MVA).HIVA and MVA.RENTA, delivered in a heterologous DNA prime-MVA boost regimen. While the HIVA (Gag/epitopes) components have been tested in NHP and over 300 human subjects, we plan to test in humans the RENTA (reverse transcriptase, gp41, Nef, Tat) vaccines designed to broaden HIVA-induced responses in year 2007. Here, we investigated the four-component vaccine long-term immunogenicity in Mamu-A*01-positive rhesus macaques and demonstrated that the vaccine-induced T cells were multi-specific, multi-functional, readily proliferated to recall peptides and were circulating in the peripheral blood of vaccine recipients over 1 year after vaccine administration. The consensus clade A-elicited T cells recognized 50% of tested epitope variants from other HIV-1 clades. Thus, the DNA-MVA/HIVA-RENTA vaccine induced memory T cells of desirable characteristics and similarities to those induced in humans by HIVA vaccines alone; however, single-clade vaccines may not elicit sufficiently cross-reactive responses.